PROFIL PEMBELAJARAN MEMBACA PEMAHAMAN DI KELAS IV SEKOLAH DASAR - Imam Agus Basuki (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2011)
Abstract: This case study aims at describing reading-comprehension teaching models and their activities. The research involved twelve schools in five provinces in Indonesia. The data being collected in the research were in the forms of video recording of teaching and learning activities, in which teachers carried out reading-comprehension teaching activities by engaging students in them. The data on teachers and students' activities were then identified, classified, and generalized. The results show that there are four learning models being used in the teaching of reading-comprehension at the elementary schools being researched. The first model involves comprehending while reading the text, teacher providing explanation concerning content, students answering questions and retelling the content. The second model involves discussion on the title, students taking turn reading the text, finding details, and answering questions. The third involves students reading out loud together, teacher explaining the content, word game, finding main idea(s), doing exercises, and writing a composition based on pictures being provided. The fourth involves silent reading, retelling exercise, retelling before class, and rewriting the text.   Abstrak: Penelitian ini bertujuan untuk mendeskripsikan pola/model pembelajaran membaca pemahaman di SD, serta aktivitasnya. Penelitian studi kasus ini melibatkan 12 sekolah dari 5 provinsi. Sumber data berupa rekaman pembelajaran membaca pemahaman yang merupakan tampilan guru secara maksimal. Data yang berupa aktivitas guru dan siswa dianalisis dengan langkah identifikasi, kalsifikasi, dan generalisasi. Hasil analisis menunjukkan terdapat empat pola pembelajaran membaca pemahaman. Pola pertama adalah menyimak sambil membaca teks, dijelaskan isinya, menjawab soal, dan menceritakan isi. Pola kedua adalah membahas judul, bergantian membacakan teks, mencari isi paragraf, menjawab pertanyaan, dan bergantian membacakan teks. Pola ketiga adalah  membaca keras bersama-sama,  dijelaskan isinya, permainan kata, mencari pokok pikiran, mengerjakan latihan, dan mengarang berdasarkan gambar. Pola keempat adalah  membaca dalam hati, berlatih bercerita, bercerita di depan kelas, dan menuliskan kembali isi cerita.